THE EFFECT OF PROFITABILITY ON WORKING CAPITAL MANAGEMENT AND COMPANY CAPITAL STRUCTURE - Elwisam; Melati; Rahayu Lestari; Kumba Digdowiseiso; Rosyidah Muhammad (RADJA PUBLIKA, 2024)
The significance lies in comprehending the correlation between profitability, working capital management, and capital structure within the framework of corporate financial decision-making. This study aims to elucidate the influence of profitability on the efficiency of working capital management and the policy regarding capital structure. The employed approach is Systematic Literature Review (SLR), which involves the identification, selection, and evaluation of pertinent scientific literature. The findings indicate that the profitability level has an impact on a company's capacity to handle working capital, affects the cash cycle, and can elucidate decisions regarding capital structure policy. While high profitability enables increased access to external financial resources, low profitability can present difficulties in managing working capital. The discussion encompasses the practical ramifications of these findings, such as implementing astute financial strategies to enhance profitability and optimize the management of working capital. Ultimately, this study offers a comprehensive perspective on the correlation among profitability, working capital management, and capital structure. Acquiring this knowledge is crucial for companies to make informed financial decisions and guarantee long-term viability and steady expansion in a constantly changing business landscape.